Using Net Linkages in Explaining the Position of Banking Sector in the Economy of Iran - Zahra Mosayyebi; Nooraddin Sharify (فصلنامه پژوهش‌های اقتصادی ایران, 2017)
Developing countries are faced with the scarcity of resources such as labor force, investment, energy, water, etc. Such scarcities have forced these countries into adopting the unbalanced growth theory and prioritizing their resources in the manufacturing sectors. In this study, the importance of the banking sector in Iranian economy, as well as its effects on other economic sectors are taken into account. Total forward Linkages (Net and Gross) are used in order to specify the influence of the banking sector on other sectors, and also to compare it with them. The stimulation of the development of banking sector activities on the various economic sectors is also specified through total backward linkages (Net and Gross). The statistical data of this study have been provided from the input-output table (2012); the latest official updated input-output table of Iran, released by Iran’s Parliament Research Center. The position of this sector, both in terms of stimulatibility and stimulation in the manufacturing sectors, is lower than that of other sectors. The partial forward linkage index of the banking sector shows that 67.93% of the banking services are used as intermediate goods in the economy. Thus, the banking sector is the one which that is mostly at the service of the production sectors, and in this regard, it is ranked first among all service sectors. The chemical production, building and banking sectors respectively obtain the most benefits from banking services. The chemical production sector, the banking sector and the water, electricity and the natural gas distribution sectors, respectively, are the largest suppliers of the banking sector’s needs.